An approach for cancer risk-based apportionment of PM2.5 constituents and sources. Issue 2 (4th March 2022) - Pathak, Ashutosh K; Sharma, Mukesh; Nagar, Pavan K
Abstract: The primary concern of PM2.5 (particle size of an aerodynamic diameter 2.5 micrometers or less) is its adverse health effects. As not all PM2.5 particles are equally toxic, a uniform PM2.5 mass control across the emitting sources may not provide the maximum health benefits. A new approach that apportions PM2.5 constituents, based on their toxicity and further realigns them into the sources, is developed and applied to Delhi city. In PM2.5, concentrations of 81 constituents in 11 apportioned sources were derived. Fourteen carcinogen constituents (Pb, Cr, Ni, Cd, As, Co and eight PAHs) were considered. The USEPA's CompTox was used to obtain the cancer threshold concentration ( Cca ) of the constituents. A product of constituent concentration and the inverse of Cca yielded constituent-wise cancer potential ( CCPca ). The source-wise cancer potential was 20% for diesel, 19% for road dust, 16% for coal power plant, 13% for municipal solid waste burning and 8% for gasoline vehicles. Among 14 carcinogen constituents, Cr accounted for 20% of mass but showed the maximum CCPca . The net incremental lifetime cancer risk ( NILCR ) for all sources was 4.2 × 10 −4 . Diesel showed the maximum NILCR at 8.5 × 10 −5 and liquid petroleum gas lowest at 8.8 × 10 −6 .